Improving the Effectiveness of the Music Team and Song Leader through Worship Service Coordination Training at HKBP Immanuel Patumbak Church - Ance Juliet Panggabean; Samsa Lumbangaol; Thesa Angelica Siahaan (Samakta: Jurnal Pengabdian Kepada Masyarakat, 2026)
This community service activity highlights the importance of synergy between the music team and song leaders (SL) in worship services at HKBP Immanuel Patumbak Church. Music plays a central role not only as a complement to liturgy, but also as a means of expressing faith and uniting the congregation in praise to God. However, there is still a gap between church music theory and practice, where coordination between music ministers is often ineffective and theological understanding of the role of music in worship is still limited. Based on these conditions, this activity aims to empower music ministers and SLs to improve coordination, deepen theological understanding, and strengthen spiritual motivation in ministry. The approach used is participatory and reflective, with methods including lectures, technical training, worship simulations, and joint reflection. The social engineering strategy is carried out through the formation of new patterns of cooperation that are more synergistic and communicative among ministry team members. The activity was held on August 18, 2025, involving 50 participants consisting of musicians, song leaders, and congregants. The results of the activity showed a significant increase in the participants' coordination skills, theological awareness, and enthusiasm for ministry. In addition, a sense of togetherness was created that strengthened the quality of worship and music ministry in the church. In conclusion, this service successfully bridged the gap between church music theory and practice and became an effective empowerment model in building synergy in church music ministry based on spirituality and professionalism.